2020
DOI: 10.1016/j.rbmo.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of the risk of SARS-CoV-2 infection in an IVF laboratory

Abstract: This failure modes and effects analysis describes the precautionary administrative measures, the additional personal protective equipment required, and the modifications of IVF laboratory settings and procedures required to reduce the risk of aerosol-mediated viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Four main areas of potential 2-way infection have been identified, i.e., patient-staff, staff-staff, staff-cell, and cell-cell. The results of a failure modes and effect analysis conducted by a multidisciplinary IVF team showed that, except for cell-cell contamination, which is considered extremely unlikely, patient-employee, employee-employee, and employee-cell interaction periods are estimated to have a moderate to high infection risk [50]. Therefore, routine SARS-CoV-2 tests for patients and providers are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Four main areas of potential 2-way infection have been identified, i.e., patient-staff, staff-staff, staff-cell, and cell-cell. The results of a failure modes and effect analysis conducted by a multidisciplinary IVF team showed that, except for cell-cell contamination, which is considered extremely unlikely, patient-employee, employee-employee, and employee-cell interaction periods are estimated to have a moderate to high infection risk [50]. Therefore, routine SARS-CoV-2 tests for patients and providers are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…While the ART fraternity debates on resumption of services and struggles with strategies, one must keep in mind that ART pregnancies may not be absolutely protected from SARS-CoV-2 [39-41]. There is evidence of the presence of SARS-CoV-2 receptors in both female and male genital tract and gametes; the virus is detected in semen and may cause gonadal dysfunction [42-45].…”
Section: Discussionmentioning
confidence: 99%
“…While the ART fraternity debates on resumption of services and struggles with strategies, one must keep in mind that ART pregnancies may not be absolutely protected from SARS-CoV-2 [39][40][41].…”
Section: Ivf Treatment Detailsmentioning
confidence: 99%
“…[ 13 14 15 16 17 ] While the ART pregnancies are not absolutely protected from SARS-CoV-2, the possibility of vertical transmission from an IVF clinic may be negligible. [ 18 19 20 21 ] Presence of SARS-CoV-2 receptors in both female and male genital tract and gametes, and permissibility of trophectoderm and early placenta to the virus are of concern for ART fraternity. [ 22 23 24 25 26 27 28 29 30 ] The available evidence should be a part of pretreatment communication with couples planning ART.…”
Section: Introductionmentioning
confidence: 99%